Komunikasi word of mouth (wom) sebagai penentu keputusan pembelian konsumen - Wibowo, Arief; Satiri; Poppy Ruliana; Kresno Yulianto (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this study was to determine the effect of Word Of Mouth (WOM) communication on purchasing decisions at NanoKomputer. NanoKomputer is a shop that has a focus on selling electronic goods in the form of computers and other office needs, researchers argue that NanoKomputer uses a method of delivering messages to consumers by word of mouth, because NanoKomputers do not have open sales suppression activities, but NanoKomputers often become recommendations from several sources as well as several information technology forums. The method used is to conduct a survey given to the group object to be studied. This research design has a purpose to find the effect between two variables, namely Variable (X) is Word of Mouth while variable (Y) is Purchase Decision. Respondents involved in this study were employees of the Depok Kartini Office Complex as many as 96 people. The sampling method used purposive sampling. Data collection using a questionnaire will be given to several employees in the Kartini Citayam Office Complex, Depok. The results of the study indicate that there is a positive influence between the Word Of Mouth (WOM) variable on purchasing decisions which is supported by the results of surveys and statistical calculations using SPSS software, in other words all employees of the Kartini Depok Office Complex who buy computer needs at NanoKomputer are influenced by communication. Word of Mouth.